Wage Bargaining, Labor Turnover, and the Business Cycle: A Model with Asymmetric Information - Perry, Motty; Solon, Gary (Journal of Labor Economics, 1985)
This paper presents a wage-bargaining model in which the employer and employee are each uncertain about the other's reservation wage. Under specified circumstances, the model's equilibrium is shown to involve unilateral wage setting and inefficient labor turnover. In addition, aggregate demand shocks affect the equilibrium in a way that produces procyclical quits and countercyclical layoffs. These results are obtained without resorting to assumptions of nominal wage rigidity, long-term contracting, or aggregate price misperceptions.